A ANALISIS KESALAHAN BERBAHASA PADA ARTIKEL “IMPLEMENTASI KURIKULUM MERDEKA (IKM) PADA PEMBELAJARAN BAHASA INDONESIA DI SMA NEGERI 1 GEMOLONG": Analisis Kesalahan Berbahasa - Ramadhani, Nova Putri (Jurnal Pena Indonesia, 2024)
The aim of this study was to find out the language errors in the article entitled Implementation of Independent Curriculum (IKM) In Indonesian Language Learning At SMA Negeri 1 Gemolong. The method used is a descriptive qualitative method with data collection using the read note technique, by reading the article that is the object of analysis, then noting the parts that contain language errors. The object of this study is the content of the article Implementation of Independent Curriculum (IKM) On Indonesian Language Learning At SMA Negeri 1 Gemolong. The conclusion of this study is that there are still some language errors that should be noted. The first error is related to the writing of capital letters, the second is related to the writing of italics, the third is related to the use of comma punctuation, and the fourth is related to the writing error of the word. This fact indicates that the article still does not comply with the rules set forth in the Enhanced Spelling V edition, especially in aspects of language writing, words, and punctuation usage